PENGEMBANGAN BAHAN AJAR DI PERGURUAN TINGGI - Wahyu Sri Ambar Arum (Perspektif Ilmu Pendidikan, 2006)
In competency based learning, instructional materials play an important role in helping students achieving a set of competencies. Therefore the instructional materials should be prepared as good as possible. this article will discuss the role and definition of instructional materials, the principles and the steps of instructional material selection, the sources of instructional materials, the scope and the sequence of instructional materials, the strategies of using it, and finally the forms of instructional materials.